(untitled) (Journal of Geography and Environmental Management, 2021)
Ozone control and monitoring are very important because they provide the world’s population with a basis for making informed decisions and policies to protect life on earth. Since the thinning of the ozone layer is harmful to nature and human health, the study of the spatial and temporal dynamics of stratospheric ozone on the territory of Kazakhstan does not lose its significance. Based on aerological data obtained from observations of the world ozone and ultraviolet data center and the University of Wyoming, the total amount of ozone and its relationship with other meteorological parameters (air temperature above 20 km altitude, relative humidity and wind speed) at stations where ozone observations are carried out in Kazakhstan were investigated and the correlation between them was calculated. Correlation analysis of control series was used to study the relationships between values, hypotheses were made about possible mechanisms of their interaction, and the method of statistical processing was used as a research method. The average annual moves of the considered characteristics are given. As a result, it was found that each of the considered meteorological parameters affects the ozone concentration, especially in close connection with changes in air temperature. Under the influence of strong heating of the stratosphere, a positive relationship between the air temperature and the total ozone was revealed, while under normal conditions it has a negative relationship.